Redefining Microglial Identity in Health and Disease at Single-Cell Resolution. Issue 1 (January 2021) - Provenzano, Francesca; Pérez, María José; Deleidi, Michela
Abstract : Microglia have long been considered a homogenous cell population that uniformly responds to extrinsic factors. Here, we describe how the recent development of single-cell technologies has revealed the heterogeneity of both human and mouse microglia and identified distinct microglial states linked to specific developmental, aging, and disease stages. We discuss progress and future developments in data analysis, essential tools for the comprehension of big data derived from single-cell omics, and the necessity of integrating such data with functional studies to correlate genetic cues with the relevant biological functions of microglia. Defining the functional correlates of distinct microglia states is fundamental to dissecting the 'microglial etiology' of aging and complex neurological diseases and identifying novel therapeutic and diagnostic targets. Highlights: Single-cell technologies have recently led to the identification of multiple microglial states characterized by defined signatures in both mouse and human tissues. Microglia are a highly heterogeneous cell population that is much more complex and plastic than previously thought. Distinct microglial states linked to developmental, aging, and disease stages can be identified in different brain regions. Novel spatial multiomics platforms, which allow the study of single cells in their native microenvironments, thus preserving spatial information, are being developed. These technologies provide the possibility of evaluating tissue architecture and intercellular crosstalk. The ability to identify individual immune cells in the central nervous system facilitates the discovery of key pathways underlying neuronal vulnerability to disease, which can be exploited for drug discovery.